2015
DOI: 10.1126/scisignal.aab3156
|View full text |Cite
|
Sign up to set email alerts
|

The early synthesis of p35 and activation of CDK5 in LPS-stimulated macrophages suppresses interleukin-10 production

Abstract: Interleukin-10 (IL-10) is an important anti-inflammatory cytokine that is produced primarily by macrophages. We investigated mechanisms by which the timing of IL-10 production was controlled in macrophages and found that cyclin-dependent kinase 5 (CDK5) activity was markedly increased in lipopolysaccharide (LPS)-stimulated macrophages through the synthesis of the CDK5-binding partner and activator p35. Degradation of p35 released the inhibition on anti-inflammatory signaling mediated by CDK5-p35 complexes. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 44 publications
2
39
1
Order By: Relevance
“…Given the presence of an AP-1 consensus motif in Il10 and the evidence that potentiation of MAP kinase signaling can increase IL-10 production 1,10,11 , we hypothesized that an increase in AP-1 activity resulting from reduced c-Jun Ser243 phosphorylation may mediate activation of IL-10 following CDK8 inhibition. Supporting this theory, we found that co-treatment of BMDCs with dCA and T-5224 (8), a small-molecule inhibitor of AP-1 reported to bind c-Fos and inhibit its dimerization with c-Jun 32 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the presence of an AP-1 consensus motif in Il10 and the evidence that potentiation of MAP kinase signaling can increase IL-10 production 1,10,11 , we hypothesized that an increase in AP-1 activity resulting from reduced c-Jun Ser243 phosphorylation may mediate activation of IL-10 following CDK8 inhibition. Supporting this theory, we found that co-treatment of BMDCs with dCA and T-5224 (8), a small-molecule inhibitor of AP-1 reported to bind c-Fos and inhibit its dimerization with c-Jun 32 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, amplification of mitogen-activated-protein (MAP) kinase signaling by perturbation of microtubule dynamics or inhibition of cyclin-dependent kinase 5 (CDK5) can also upregulate IL-10 (refs. 10,11 ). Notably, these probes have identified therapeutically useful drug targets, exemplified by approval of the PDE4 inhibitor apremilast for treatment of psoriatic arthritis as well as preclinical evaluation for treatment of IBD 12,13 .…”
mentioning
confidence: 99%
“…Specifically, Cdk5 activity enhances the inflammatory function of macrophage by regulating MAPK-dependent production of suppressor of cytokine signaling-3 and IL-10. 74 Although experiments mixing BM from Cdk5 2/2C donors with Cdk5 1/1C T cells resulted in a modest improvement in survival after allo-HCT (33% vs 13%, Table 1), systemic GVHD as measured by clinical score was not different between groups underscoring the predominant role of Cdk5 activity in the T-cell compartment as a determinant of GVHD severity. In summary, the accumulating evidence regarding Cdk5-dependent T-cell function has important implications for a broad spectrum of immune and inflammatory disorders.…”
Section: /2cmentioning
confidence: 93%
“…Unlike other members of the cyclindependent kinase family, Cdk5 is activated by the non-cyclin cofactor Cdk5 regulatory subunit 1 (Cdk5r1; also known as p35) (Chae et al, 1997) and is not involved in cell cycle regulation (Dhavan and Tsai, 2001;Lalioti et al, 2010). While Cdk5 has been intensively studied in the context of neural development, several studies have begun to hint at an important role outside the nervous system (Dhavan and Tsai, 2001;Na et al, 2015;Wei et al, 2005). However, the function of Cdk5 in liver development, particularly in biliary network development, has not been studied and there is no evidence yet linking Cdk5 to the pathology of biliary atresia.…”
Section: Introductionmentioning
confidence: 99%